2015
DOI: 10.3347/kjp.2015.53.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Molecular Evaluation of Pediatric Hydatid Cyst Cases in Eastern Turkey

Abstract: Cystic echinococcosis (CE) caused by Echinococcus granulosus is a major public health problem worldwide, including Turkey. The aim of the current study was to identify the strains and to estimate the potential risk factors of E. granulosus in operated pediatric cases in eastern Turkey. Ten pediatric patients (7 boys and 3 girls) living in rural areas, with ages ranging from 3 to 15 years old and various clinical histories, were included in this study. Eight patients had only liver hydatid cyst, while 1 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…As a result, all the isolates collected in this study were confirmed by BLAST algorithm as E. granulosus s.l. From Turkey, there are several reports on molecular characterization of E. granulosus s.l isolates from various intermediate hosts (Schneider et al 2008;Utuk et al 2008;Snabel et al 2009;Ergin et al 2010;Simsek et al 2011;Utuk and Simsek 2013;Bakal et al 2015;Eroglu et al 2016;Orsten et al 2018;Kurt et al 2020;Örsten et al 2020). These studies showed that E. granulosus s.s. (genotypes G1-G3) is the predominant species obtained from hydatid materials in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, all the isolates collected in this study were confirmed by BLAST algorithm as E. granulosus s.l. From Turkey, there are several reports on molecular characterization of E. granulosus s.l isolates from various intermediate hosts (Schneider et al 2008;Utuk et al 2008;Snabel et al 2009;Ergin et al 2010;Simsek et al 2011;Utuk and Simsek 2013;Bakal et al 2015;Eroglu et al 2016;Orsten et al 2018;Kurt et al 2020;Örsten et al 2020). These studies showed that E. granulosus s.s. (genotypes G1-G3) is the predominant species obtained from hydatid materials in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of research conducted on molecular identification of E. granulosus s.l. isolates from sheep, cattle, goats and humans from different regions of Turkey (Schneider et al ., 2010; Utuk et al ., 2008; Šnàbel et al ., 2009; Ergin et al ., 2010; Simsek et al ., 2011; Eryildiz and Şakru, 2012; Bakal et al ., 2015; Eroğlu et al ., 2016; Orsten et al ., 2018). According to these studies, E. granulosus s.s. (G1–G3 genotypes) was the most common species causing CE in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers indicated that G1 and G3 genotypes ( E. granulosus s.s. ) are predominant in the human host in Turkey (Utuk et al ., 2008; Snabel et al ., 2009; Ergin et al ., 2010; Simsek et al ., 2011; Eryıldız and Şakru, 2012; Bakal et al ., 2015; Eroğlu et al ., 2016; Erdoğan et al ., 2017; Oral Babaoğlu et al ., 2018; Orsten et al ., 2018). Echinococcus canadensis (G7 genotype), also known as pig strain, was reported from Turkey for the first time by Snabel et al .…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed by Bakal et al contact with dogs and poor hygiene conditions were found to be important risk factors for CE. 38 Non effective control programs for E.granulosus in dogs prevent eradication of this parasite. 39 In our study, 77.5% of all dog owners administered did not administer antiparasitic drugs to their dogs; in Sardinia, Italy, the corresponding rate was 90%.…”
Section: Discussionmentioning
confidence: 99%